SSIR’s 2021 Social Innovation Reading List (SSIR) - Stanford, University (2022)
Highlights from book excerpts published by SSIR online this year on topics including mutualism, grassroots development, breakthrough ideas, racial injustice, and well-being.
Keywords: Innovation sociale; Libre accès; Économie; États-Unis